Control of pH during water denitrification in an upflow bio-electrochemical reactor (UBER) using a pumparound system - Ghafari, S.; Aroua, M.K.; Hasan, M. (Separation and Purification Technology, 2010)
In this study a new reactor design is proposed to control the pH during the bio-electrochemical denitrification process. A previously developed UBER was modified by including a pumparound system. With the pumparound system a portion of the treated water is continuously withdrawn from the UBER into a CO 2 sparging bottle to decrease its pH to about 6.1 Â± 0.1, before being returned to the cathode zone where denitrification process takes place. Continuous denitrification was studied with a HRT of 24 h applying an electric current in the range of 15-25 mA. The effects of circulation flow rate (F c) on the pH and on the concentrations of nitrate and nitrite ions in the effluent were investigated. The pumparound system succeeded to stabilize the cathode pH around 7-8 through alteration of circulation flow rate (F c). Complete denitrification with no trace of nitrite was therefore achieved at circulation flow rate of 0.7 mL/min and electric current 25 mA. A further investigation in absence of bicarbonate sodium resulted in a satisfactory nitrate treatment showing that the carbon dioxide gas dissolved in the CO 2 sparging bottle supplied enough carbon for the autohydrogenotrophic microorganisms.